Failure Behavior of Masonry Wall under Bidirectional Forces - Sookmanee, Pongsak; Chusilp, Nuntachai (Engineering and Technology Horizons, 2023)
The objective of this research is to investigate the failure behavior of masonry walls under bidirectional forces (vertical and lateral loads) for application in the construction of small community buildings with limited load-bearing capacity. To achieve this, three types of bricks, namely clay bricks, lightweight bricks, and block bricks, were subjected to testing in accordance with industrial product standards specific to each brick type. These tests aimed to assess the load-bearing capacity of masonry walls, utilizing full-sheet and half-sheet walls with dimensions of 1.0 meter ×1.0 meter, available in three different styles: 1) walls without gaps, 2) walls with window openings, and 3) walls with door openings, all designed to endure both vertical and lateral forces. The study's findings revealed that the primary mode of failure was attributed to diagonal shear failure, primarily induced by lateral forces rather than vertical ones. Masonry walls subjected to vertical forces displayed no signs of cracking because this was a non-destructive test. In contrast, masonry walls subjected to lateral forces exhibited cracks in diagonal patterns and straight lines as the predominant forms. Notably, both half-sheet and full-sheet brick walls exhibited more prominent cracks compared to block brick walls and lightweight bricks. Cracking was observed in the interfaces between the bricks and the mortar, as well as within the bricks and mortar themselves. Furthermore, it was observed that brick walls with window and door openings had 82 and 76 percent of the brick area compared to walls without gaps, respectively. These walls were able to withstand forces until failure, approximately 48 and 70 percent less on average. Lastly, the study highlighted that the strength of a brick wall is contingent on the tensile strength of the bricks and the shear strength of the mortar.